International Banking Strategy and Efficiency: issues and directions. - Phelps, Bob; Figueira, Catarina; Nellis, Joseph G. (Cranfield University, 2003)
This paper reviews measures of banking efficiency and analyses the efficiency construct and its applications. We discuss the issues of data availability and methodological problems that occur when trying to obtain realistic local and global efficiency indicators for banks. We conclude by suggesting directions for future research that both inform theory and have practical application.